Fluid Justice: Tracing The Experiences Of Women Navigating Urban Water Insecurity In Luveve In Bulawayo, Zimbabwe - Dube, Gugulethu Violet (University of the Witwatersrand, Johannesburg, 2024)
Water insecurity, exacerbated by population growth and climate change, poses significant global challenges. Especially in developing countries, where decreasing water supply, contaminated sources and inadequate infrastructure disproportionately affect vulnerable populations. Women, often primary caregivers, bear the brunt of these challenges as they are typically responsible for water collection, impacting their educational and economic opportunities. This report delves into the complex impact of water insecurity on women in an urban township in Luveve, Bulawayo, while also addressing the broader issue of global water insecurity and advocating for water access as a fundamental human right essential for poverty reduction. Employing a combination of semi-structured interviews, critical reading, and a feminist lens rooted in Social Reproduction Theory (S.R.T.) and Feminist Political Ecology (F.P.E.) alongside urban vulnerability theory, I explore the interplay between gender and water access. Our findings challenge the conventional narrative surrounding women's vulnerabilities to water insecurity, revealing diverse experiences shaped by factors like gender, socio-economic status, and household and community dynamics. Informed by these insights, the report identifies key challenges and proposes context-specific interventions to address women's needs in urban townships. By incorporating these interventions, development practitioners can advance more equitable and practical solutions, driving the empowerment and resilience of women grappling with water insecurity in developing country contexts. At the heart of this objective lies the concept of "fluid justice," which I define as the dynamic and context-specific pursuit of fairness and equity in water access, distribution, and management. This principle underscores the commitment to exploring nuanced and responsive approaches to tackling water insecurity, ensuring that interventions are sensitive to affected communities' diverse needs and experiences.
A research report Submitted in fulfillment of the requirements for a Master of Arts Development Sociology, In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Water insecurity; Gender; Women; Urban Vulnerability; Social Reproduction Theory; Feminist Political Ecology; Luveve; Bulawayo; Zimbabwe; SDG-5: Gender equality